Software/hardware interactive learning for oscilloscope - Zou, Deyi (Nanyang Technological University, 2022)
An oscilloscope is a widely used laboratory instrument, it is commonly used to analyse and display the waveform of an electronic signal and shows the voltage change over time. As many engineering students do not have prior engineering background for the most part (due to the fact that students may come from a junior college background), they may not know how to operate an oscilloscope properly and the mechanism behind it.